Financial incentives, the timing of births, birth complications, and newborn's health: Evidence from the abolition of Austria's baby bonus - Beatrice Brunner; Andreas Kuhn (University of Zurich, Department of Economics, 2011)
We analyze the fertility and health effects resulting from the abolition of the Austrian baby bonus in January 1997. The abolition of the benefit was publicly announced about ten months in advance, creating the opportunity for prospective parents to (re-)schedule conceptions accordingly. We find robust evidence that, within the month before the abolition, about 8% more children were born as a result of (re-)scheduling conceptions. At the same time, there is no evidence that mothers deliberately manipulated the date of birth through medical intervention. We also find a substantial and significant increase in the fraction of birth complications, but no evidence for any resulting adverse effects on newborns' health.
Keywords: H31; J13; 330; baby bonus; scheduling of conceptions; timing of births; policy announcement; abolition effect; birth complications; medical intervention; Kinder; Familienleistungsausgleich; Ökonomischer Anreiz; Familienplanung; Privater Haushalt; Österreich